Androgenic alopecia in post-menopausal female: a clinical presentation - Nahar, Kirty; Bohra, Usha; Arya, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Androgenic alopecia is a patterned hair loss occurring due to systemic androgens and genetic factors. It is the most common cause of hair loss in both genders. The appearance of this condition is the cause of significant stress and psychological problems, making appropriate management important. A 68-year-old postmenopausal female presented with complaints of increased hair loss from scalp, excessive hair growth at undesired sites and hirsutism not corrected with medications. On thorough investigations, CT scan whole abdomen and endocrinological workup, a clinical diagnosis of alopecia and hirsutism due to hyperandrogenemia secondary to ovarian tumor made. Abdominal hysterectomy with B/L salpingo-oophorectomy was done. Histopathological examination revealed an encapsulated tumor in right ovary-sex cord stromal tumor consistent with Leydig cell tumor in right ovary, no evidence of malignancy. Left ovary was normal. Patient showed significant regression of clinical signs and symptoms on follow up after 1 month. All women with severe hirsutism or androgenic alopecia needs further work up to locate the source of androgen over production.